IMPLEMENTASI ALGORITMA ELGAMAL DENGAN PEMBANGKIT BILANGAN PRIMA LEHMANN DAN ALGORITMA LEAST SIGNIFICANT BIT (LSB) DENGAN COVER IMAGE BITMAP UNTUK KEAMANAN DATA TEXT - Rahmansyah, Edi (JURIKOM (Jurnal Riset Komputer), 2019)
Encryption is the process of securing an information by making the information into a random form so that the information content cannot be read or understood. Algorithms used for encryption have evolved, ranging from classical algorithms to modern algorithms. But encryption still has weaknesses, one of which is the result of encryption will produce a random character which will raise suspicion that the information is important information. Cryptanalysis is a technique used to solve cryptography, where random data can be returned to the original data, so cryptography is not entirely safe. Because of these shortcomings, data security techniques are also developed by inserting information into media such as images or videos so that the information is not visible, the technique is called steganography. Steganalysis is a technique used to find out whether an image has information that is inserted, so that with this technique steganography is not fully safe.